The natural history of progressive fibrosing interstitial lung diseases - Kolb, Martin; Vašáková, Martina (Respiratory research, 2019)
A proportion of patients with certain types of interstitial lung disease (ILD), including chronic hypersensitivity pneumonitis and ILDs associated with autoimmune diseases, develop a progressive fibrosing phenotype that shows similarities in clinical course to idiopathic pulmonary fibrosis. Irrespective of the clinical diagnosis, these progressive fibrosing ILDs show commonalities in the underlying pathogenetic mechanisms that drive a self-sustaining process of pulmonary fibrosis. The natural history of progressive fibrosing ILDs is characterized by decline in lung function, worsening of symptoms and health-related quality of life, and early mortality. Greater impairment in forced vital capacity or diffusion capacity of the lungs for carbon monoxide, and a greater extent of fibrotic changes on a computed tomography scan, are predictors of mortality in patients with fibrosing ILDs. However, the course of these diseases is heterogenous and cannot accurately be predicted for an individual patient. Data from ongoing clinical trials and patient registries will provide a better understanding of the clinical course and impact of progressive fibrosing ILDs.
Keywords: rizikové faktory; hypersenzitivní pneumonitida; Risk Factors; lidé; Idiopathic Pulmonary Fibrosis; Alveolitis, Extrinsic Allergic; progrese nemoci; Lung Diseases, Interstitial; idiopatická plicní fibróza; Mortality; Disease Progression; intersticiální plicní nemoci; mortalita; Humans